Recasamento e filhos adolescentes: um estilo de vida em negociação - Cury, Christina Manço (2008)
In this work, we investigated family relationships in remarriages through the eyes of adolescent children. The rise in the number of divorces and remarriages during this period of life, as well as the shortage of research within this population, led us to investigate the problem through a qualitative research outlined with a case study. The study was made in Santos, with the participation of three youngsters, using semi-structured interviews and the Genograms of the family for data gathering. Patterns of communication, rules and loyalty were investigated as categories for this study, with the objective of understanding their meanings and the way in which the remarried family negotiated them in the view of the adolescent. The results showed that remarried families with adolescent children have a particular style of life, characterized by this particular moment, in which all the members living together shared similar conflicts, but who sought through the remarriage, alternatives to the evolution and protection of its members